Human Activity Changes During COVID‐19 Lockdown in China—A View From Nighttime Light - Xuejun Wang; Guangjian Yan; Xihan Mu; Donghui Xie; Jiachen Xu; Zhiyu Zhang; Dingdan Zhang (GeoHealth, 2022)
Abstract Strict lockdowns were implemented in China to fight Coronavirus Disease 2019 (COVID‐19). We explored the nighttime light (NTL) of China's four cities in five stages of COVID‐19 including case free period, newly appeared period, rising period, outbreak period, and stationary period. Using six categories of points of interest data (“company,” “recreation,” “healthcare,” “residence,” “shopping,” and “traffic facility”) and random forest models, we found that dimming light of four cities is associated with the epidemic development and human activity changes. When confirmed cases appeared, healthcare associated NTL radiance increased rapidly in Wuhan and Guangzhou, but decreased in the fourth and fifth stages. Companies in all cities were resuscitated in the fifth stage, while companies in Guangzhou was resuscitated in the fourth stage. Shopping related NTL radiance in Wuhan increased quickly in the fifth stage which indicated some resuscitation. In addition, compared to gross domestic product, the trend in electric power consumption was consistent with the trend in NTL radiance. The above findings contribute to the making of control policies for COVID‐19 as well as other infectious diseases.